Social and HIV/AIDS risk behaviours in a fishing community - Samsuddin, Niza; Ali, Aishah; Md Aris, Mohd Aznan; Draman, Samsul; Akter, Seikh Farid Uddin (Centre for Promoting Ideas, USA, 2011)
Background: This study was to explore the pattern and depth of social and health risk problems that may address the social drivers of HIV/AIDS in a fishing community in the East Coast of Peninsular Malaysia. Methods: Five focus group discussions were held among selected villagers to gain their experiences and perception on social problems and HIV/AIDS risk behaviours in their community. Results: Many participants discussed on early involvement in substance use disorders and high risk sexual behaviours. Participants were frustrated with the poor parental supervision and lack of social support in the community which exposed them to social problems and subsequently to risk of HIV/AIDS infections. Conclusion: Poor parental supervision and lack of social support from the community are factors need to be considered when designing structural intervention programme. Further research needs to be done among more specific target groups in villages like youths, parents and school children, in order to identify the causal chains of deeper structure of HIV/AIDS risk for proximal and distal risk factors intervention.